2021
DOI: 10.1007/s00330-021-08387-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of diffusion-weighted magnetic resonance imaging in evaluation of early therapeutic response after CT-guided microwave ablation of inoperable lung neoplasms

Abstract: Objective To determine the early treatment response after microwave ablation (MWA) of inoperable lung neoplasms using the apparent diffusion coefficient (ADC) value calculated 24 h after the ablation. Materials and methods This retrospective study included 47 patients with 68 lung lesions, who underwent percutaneous MWA from January 2008 to December 2017. Evaluation of the lesions was done using MRI including DWI sequence with ADC value calculation pre-abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…MR-guided MWA for lung malignant tumor could also be another option, just previously explored in rabbits ( 20 , 21 ). Lin et al.…”
Section: Technical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…MR-guided MWA for lung malignant tumor could also be another option, just previously explored in rabbits ( 20 , 21 ). Lin et al.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…A topic that could be interesting in the treatment of lung tumors with MWA is also represented by the ability to predict and evaluate the treatment efficacy. In detail, apparent diffusion coefficient (ADC) of MRI calculated 24 hours after MWA of lung cancer could be effectively used to predict the early treatment efficacy ( 20 ).…”
Section: Image Evaluationmentioning
confidence: 99%
“…42,45,49 On DWI, viable tissue presents as focal signal in the ablation zone, while necrotic tissue presents as a lack of signal. Two groups have shown that changes in ADC from 2 days pre-MWA/ 4 days pre-RFA to 24 hours post-MWA/ 3 days post-RFA can predict the treatment response in lung tumors before a change in tumor size becomes detectable on CT. 44,46 Postablation ADC was significantly lower in incompletely treated tumors compared with completely treated tumors and a small decrease in ADC value several days after heat-based ablation may suggest that local progression is likely on follow-up CT. There was no statistically significant correlation regarding the ADC value performed before the ablation between the responding and nonresponding tumors.…”
Section: Expected Appearance Of Lung Ablation Zones Over Timementioning
confidence: 99%
“…[42][43][44] Data following MWA in the lung are limited to a comparison of findings on CE MRI and NCE CT of 77 tumors in 49 patients as well as DWI of 68 tumors in 47 patients, both at 24-hour post-ablation. 45,46 After lung cryoablation, 35 lung tumors in 30 patients were followed up for a median of 22 months (range, 3 to 62 mo) using a CE 3.0 T MRI and a scanner with unspecified field strength (Table 3). 48,49…”
Section: Follow-up With Mri After Lung Ablationmentioning
confidence: 99%
See 1 more Smart Citation